2006
DOI: 10.1177/154405910608500108
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Nociceptors Express TLR-4 and CD14: a Mechanism for Pain due to Infection

Abstract: Although certain bacterial species appear to be risk factors for pain due to odontogenic infections, comparatively little is known about the potential mechanisms mediating this effect. In this study, we tested the hypothesis that trigeminal nociceptive neurons express the TLR4 or CD14 receptors, thus enabling sensory neurons to detect and respond to tissue levels of bacterial substances such as lipopolysaccharide (LPS). Immunohistochemical analyses of human and rat trigeminal neurons demonstrated that a capsai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(181 citation statements)
references
References 34 publications
5
173
2
1
Order By: Relevance
“…These activated microglia, in turn, release TNF-α, which induces neuron apoptosis in a caspase-3 dependent pathway [70]. There is a growing body of evidence that many neuronal subpopulations express TLRs, including TLR4 [132][133][134][135]. Mice with a defect in TLR4 are generally more resistant to CNS trauma [62], suggesting that TLR4 activation is detrimental to neuronal survival.…”
Section: Neuronsmentioning
confidence: 99%
“…These activated microglia, in turn, release TNF-α, which induces neuron apoptosis in a caspase-3 dependent pathway [70]. There is a growing body of evidence that many neuronal subpopulations express TLRs, including TLR4 [132][133][134][135]. Mice with a defect in TLR4 are generally more resistant to CNS trauma [62], suggesting that TLR4 activation is detrimental to neuronal survival.…”
Section: Neuronsmentioning
confidence: 99%
“…In neuronal cells, LPS-induced inflammation causes neuronal loss and impaired memory (Hauss-Wegrzyniak et al, 1998;Monje et al, 2003). Recent studies have indicated that TLR-3 or TLR-4 is expressed in neurons (Maoeliñska et al, 2004;Wadachi and Hargreaves, 2006); however, the detailed processes regulated by these receptors remain unknown. In this study, the prefrontal cortex in rats and cultured cortical neurons were treated with LPS to assess the relationship between neuroinflammation and NR1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…These activated microglia, in turn, release TNF-α, which induces neuron apoptosis in a caspase-3 dependent pathway [70]. There is a growing body of evidence that many neuronal subpopulations express TLRs, including TLR4 [132][133][134][135]. Mice with a defect in TLR4 are generally more resistant to CNS trauma [62], suggesting that TLR4 activation is detrimental to neuronal survival.…”
Section: Neuronsmentioning
confidence: 99%